Copper Nanowires: A Transparent and Flexible Capacitive‐Force Touch Pad from High‐Aspect‐Ratio Copper Nanowires with Enhanced Oxidation Resistance for Applications in Wearable Electronics (Small Methods 7/2018). Issue 7 (12th July 2018) - Kim, Dongkwan; Kwon, Jinhyeong; Jung, Jinwook; Kim, Kyunkyu; Lee, Habeom; Yeo, Junyeob; Hong, Sukjoon; Han, Seungyong; Ko, Seung Hwan
Abstract : In article number1800077, Seungyong Han, Seung Hwan Ko, and co‐workers report a novel copper‐nanowire synthesis method development to control both the nanowire morphology and the synthesis yield, together with their application as a highly flexible and transparent conductor for a capacitive‐type touch sensor. The copper‐nanowire transparent conductor shows an enhanced oxidation resistance by coating it with a UV‐curable polyurethane acrylate resin and is expected to be very useful in various flexible/wearable device applications.